2009
DOI: 10.1002/ejoc.200900768
|View full text |Cite
|
Sign up to set email alerts
|

Convenient Synthesis of N‐Terminal Tfm‐Dipeptides from Unprotected Enantiopure α‐Tfm‐Proline and α‐Tfm‐Alanine

Abstract: A convenient procedure for the synthesis of highly lipophilic dipeptide building blocks from enantiopure α‐trifluoromethyl α‐amino acids is reported. Coupling reactions at the C termini of the trifluoromethyl α‐amino acids were successfully performed with totally unprotected amino acids without formation of diketopiperazines. The synthesis of a tripeptide through a coupling reaction at the deactivated N‐terminal position was achieved. (© Wiley‐VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2009)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
52
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 37 publications
(9 reference statements)
0
52
0
Order By: Relevance
“…18 Our group has developed the stereoselective synthesis of a panel of acyclic and cyclic Tfm-AAs in enantiopure form [19][20][21][22][23][24][25][26] and is now mainly focused on the development of efficient methodologies for their incorporation into peptides. [27][28][29][30] Although α-CF 3 -alanine has been incorporated into peptides, the peptide coupling at the N-terminal position of α-CF 3 -proline has not been reported so far. We report herein our investigations about the incorporation of α-CF 3 -proline and various cyclic surrogates into short peptide sequences.…”
Section: Introductionmentioning
confidence: 93%
“…18 Our group has developed the stereoselective synthesis of a panel of acyclic and cyclic Tfm-AAs in enantiopure form [19][20][21][22][23][24][25][26] and is now mainly focused on the development of efficient methodologies for their incorporation into peptides. [27][28][29][30] Although α-CF 3 -alanine has been incorporated into peptides, the peptide coupling at the N-terminal position of α-CF 3 -proline has not been reported so far. We report herein our investigations about the incorporation of α-CF 3 -proline and various cyclic surrogates into short peptide sequences.…”
Section: Introductionmentioning
confidence: 93%
“…The poor nucleophilicity of the N α and the steric hindrance brought by the trifluoromethyl group require harsh coupling conditions or completely new coupling strategies (Hollweck et al 1997;Burger et al 1998) limiting their use by the peptide chemists community. To our knowledge, the incorporation of an enantiopure α-Tfm-AA at its C and N position in a peptide chain has been very scarcely reported in the literature (Koksch et al 2004;Chaume et al 2009;Botz et al 2015). Considered as an aminoisobutyric acid (Aib) fluorinated analogue, the α-trifluoromethylalanine provided an improved resistance towards chymotrypsin digestion when incorporated into a model peptide (Koksch et al 1997).…”
Section: Introductionmentioning
confidence: 96%
“…After separation via chromatography on silica gel and identification of their configuration, these tripeptides were engaged in the SPPS of the antimicrobial peptide. Since several years, we are involved in the synthesis of enantiopure α-Tfm-AAs (Huguenot and Brigaud 2006;Caupene et al 2009;Simon et al 2011;Chaume et al 2009) in order to investigate the physicochemical and biological consequences of their incorporation into peptides. In this context we showed that the incorporation of a α-Tfm-proline at the N-terminal position of a MIF-1 analogue increased its biological activity Bocheva et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…As listed in Figure 1, a great variety of biologically and pharmaceutically active molecules that feature a heterocyclic segment with a CÀCF 3 stereogenic center have emerged, and some of them have been employed at the clinical trial stage. [6] For instance, trifluoromethylated analogues of ezetimibe I bearing a four-membered b-lactam nucleus were evalu-ated as good cholesterol absorption inhibitors.…”
Section: Introductionmentioning
confidence: 99%